Integrating HIV-associated neurocognitive impairment screening and health services within primary healthcare facilities in South Africa - Munsami, Adele Delysia (Department of Psychiatry and Mental Health, 2023)
Despite widespread availability of effective antiretroviral therapy (ART), people living with HIV (PWH) remain at risk of developing comorbidities including HIV-associated neurocognitive impairment (H-NCI). These individuals may then be at an increased risk for treatment non-adherence, which leads to poor quality of life and early mortality. Despite this risk, there is a paucity in trained professionals in low- and middle-income countries with appropriate knowledge and skills to identify H-NCI and make appropriate referrals for additional confirmatory testing or intervention, depending on the severity and context of the screening. General medical doctors, nurses and adherence counsellors provide most HIV related healthcare services at a primary healthcare level in South Africa. However, awareness of the clinical presentation of H-NCI, and their current screening practices among these cadres, is unclear. To address these knowledge gaps this thesis set out to explore the following aims (1) examine existing H-NCI knowledge and practices among healthcare workers delivering HIV services in South Africa, (2) develop an appropriate H-NCI training programme for primary healthcare workers, and (3) lastly, pilot the H-NCI training to determine whether H-NCI screening would be feasible at a primary healthcare level in South Africa. Methods To achieve these objectives, the study was divided into two phases. In phase one, a scoping review identified and summarised published studies addressing brain and/or behaviour training approaches, including H-NCI, targeting frontline HIV healthcare workers in Africa. An online survey was developed and administered to examine existing H-NCI knowledge and current practices among healthcare workers providing HIV services in South Africa. Focus group discussions and in-depth interviews were then conducted to explore knowledge gaps, previous H-NCI training and healthcare workers' perspectives of screening at a primary healthcare level. In phase two, an H-NCI training curriculum was developed and a work-integrated H-NCI training programme targeting primary healthcare workers was piloted. The pilot training assessed knowledge of H-NCI signs and symptoms, healthcare workers' attitude toward and comfort with H-NCI screening tools and healthcare workers ability to accurately administer an H-NCI screening tool. The assessments were repeated two months post-training to evaluate retention of knowledge and skills. Results The scoping review of the existing literature suggested that there were few brain and/ or behaviour training programs targeting healthcare workers providing HIV services in Africa. Of the ten studies identified in the scoping review, one study included H-NCI in the training curriculum. The online survey found that H-NCI knowledge was limited and screening practices virtually non-existent among healthcare workers providing HIV care in South Africa. Qualitative data gathered during the focus group discussions and the in-depth interviews provided greater insight on the existing knowledge and practices gaps as well as highlighting that healthcare workers had not received training on H-NCI. The results from the qualitative investigations showed that primary healthcare workers were in favour of receiving such training. Overall, knowledge of H-NCI improved among primary healthcare workers following the work-integrated H-NCI training programme. The training demonstrated that primary healthcare workers providing clinical services, such as medical doctors or professional nurses were able to administer an H-NCI screening tool. Although knowledge of the clinical presentation of H-NCI improved among adherence counsellors, these healthcare workers experienced challenges in administering the H-NCI screening tool. Conclusion As a body of work, the findings from this thesis suggest that healthcare professionals providing HIV services in South Africa have limited knowledge to identify H-NCI, and screening practices are uncommon. Although training revealed differences between cadres in administering screening tools, healthcare workers providing clinical care, including general medical doctors and professional nurses, may be able to provide H-NCI screening at routine annual visits. Although adherence counsellors are ideally situated in the clinic flow to provide targeted screening by flagging clinical presentation of H-NCI among PWH accessing care, this cadre will require additional training, mentorship and support to successfully administer H-NCI screening tools. However, the feasibility of H-NCI screening at a primary healthcare, timing and nature of any screening remains to be explored. This body of work is a step toward increasing the availability of skilled healthcare workers with appropriate knowledge and skills to screen and identify H-NCI in low- and middle-income countries. The work presented in this thesis provides a foundation for further development of the H-NCI training module and future investigations examining targeted screening strategies at a primary healthcare level, feasibility and access to existing interventions post-screening